Sexual Dysfunction in Unmedicated Patients with Schizophrenia and in Healthy Controls - Dembler-Stamm, Theresa; Fiebig, Jana; Heinz, Andreas; Gallinat, Jürgen (Pharmacopsychiatry, 2018)
Introduction Sexual dysfunction figures prominently in patients with schizophrenia; however, medication effects may play a role. The objective of this case control study was to assess differences in the presence of sexual dysfunction in unmedicated patients with schizophrenia versus healthy controls.Methods Sexual dysfunction was assessed using the Derogatis Inventory for Sexual Function self-rating in a cross-sectional design controlling for age and gender effects. A brief sexual anamnesis was applied to describe the psychosocial background of the mostly male sample further.Results Results show a significant difference with patients reporting more problems in most domains and with a significant correlation between severity of psychosis (Positive and Negative Syndrome Scale total scores) and the impairment of orgasm experience. The study revealed reduced sexual activities and less pleasure during sexual activities of patients.Discussion This study implies that schizophrenia has an impact on the presence of sexual dysfunction and that sexual dysfunction is partly independent of antipsychotic treatment. Since the sample consisted mostly of first-episode males, conclusions might only be valid for this subgroup.
Keywords: libido; sexual dysfunction; schizophrenia; unmedicated; DISF-SR